The Influence of E-Wallets and Hedonism in Mediating the Relationship Between Lifestyle and Impulsive Consumption Behavior Among Gen Z Students - Kamelia Astuty; Tara Julita Eka Putri; Dilla Julia Azzarah; Evi Herlyaminda (Sekolah Tinggi Ilmu Ekonomi Bentara Persada, 2026)
The purpose of this study was to determine the potential revenue projections Land and Building Tax (PBB) in the city of Batam years 2014-2016..….…(CLICK C_ABSTRACT)